A questão do ser nos Ensaios de Montaigne - Marcelo Fonseca Ribeiro de Oliveira (2016)
This dissertation inquires about an implicit ontology in Montaigne's Essays, considering the skepticism professed by this author. To achieve that, it proposes an interpretation of the main passages where the concept of being appears. For this, its structure was organized in three parts: the being of God, the being of nature and the being of man. In the first part, it analyses the fideism in the second-to-last chapter of the First Book. Fideism is traditionally attributed to the "Apology for Raymond Sebond", thesis which this dissertation also claims. In parallel to the fideism thesis itself, it suggests that there is a kind of ontological commitment that could be derived from the separation between reason and faith. The second part searched the main passages related to the notion of nature, in order to reconstruct a kind of philosophy of nature, where movement and diversity appears as the central notions. At last, in the third part the question of man is presented not without a brief overview on notions like 'appearance' and 'universal', the reality of the individuals and the issue of the subject.